Legal Responsibility for the Concurrent Crimes of Fraud and Embezzlement - Adlin, Adlin; Asmi Hasibuan, Saiful (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The legal regulation on concurrent criminal acts serves as a guideline for addressing situations where an individual commits multiple offenses that have not yet been adjudicated by the court. This regulation ensures a structured approach to resolving such cases and determining appropriate penalties. In the context of crimes such as fraud and embezzlement, concurrent penalties involve a legal assessment that views each criminal act as distinct and separate, even if they were committed in a connected or sequential manner. This perspective is crucial because it recognizes the individuality of each offense, leading to the imposition of penalties that reflect the seriousness and impact of each act. The combination of concurrent penalties thus ensures that justice is served in a manner that acknowledges the complexity and multiplicity of criminal behavior, providing a comprehensive resolution that addresses all aspects of the crime(s) committed. This approach not only upholds the principles of fairness and proportionality in sentencing but also reinforces the legal system's commitment to treating each offense with the gravity it deserves.